Dynamic Modeling and Nonlinear Vibration Research of the Rotary Cutting Mechanism Based on Bond Graphs - Zhao Jiayi; Gao Yiyang; Zhao Changzhen; Rao Xiaobo; Ding Shunliang; Gao Jianshe (Jixie chuandong)
The quality of the cut end surface of pipelines is one of the important factors to ensure the safe operation of the pipeline system. However, the existence of nonlinear factors in the pipeline cutting process may lead to chaos, quasi-periodic and other harmful vibration of the pipe cutting machine, which may affect the cutting accuracy and quality. Therefore, revealing the mechanism of dynamic instability of the pipe cutting machine to avoid the harmful vibration is the key to improve the operation performance and cutting accuracy. In this study, the dynamic model of the rotary cutting mechanism of a rotary pipe cutter is established based on the bond graph theory, the key dynamic parameters are determined by calculating the sensitivity, and the bifurcation mechanism of key parameters is revealed comprehensively by using the bifurcation diagram, the Lyapunov exponent diagram, the phase diagram and the time response diagram. The results show that with the changes of the excitation amplitude, the excitation frequency and the elastic coefficient of the base, complex dynamic behaviors such as the period-doubling bifurcation, Hopf bifurcation, the chaos and the coexistence of attractors will exist in the system, resulting in vibration and sudden change of the motion that seriously reduce cutting quality. The results provide reference for the subsequent dynamic performance optimization and vibration suppression of the mechanism.